Social Networks Use Disorder and Associations With Depression and Anxiety Symptoms: A Systematic Review of Recent Research in China - Hussain, Zaheer; Wegmann, Elisa; Yang, Haibo; Montag, Christian (Frontiers in Psychology, 2020)
Background: An increasing number of studies have investigated Internet communication disorder (ICD) among Western samples. In this context the investigation of ICD in Asia has been much neglected. This poses a gap in the literature, because it has been estimated that more than one billion Chinese persons are using social networking sites (SNSs). Of note, many of these SNSs used in Asia are rather unknown to researchers in Western countries. Aims: The primary objective of the present systematic review was to identify and evaluate Chinese studies examining the associations between ICD and depression and anxiety symptoms. Method: A comprehensive search strategy identified relevant studies in PsycINFO, PsycARTICLES, Psychology and Behavioural Sciences Collection, MEDLINE, ProQuest, ProQuest, Web of Science, PubMed, Google Scholar, and the Chinese National Knowledge Infrastructure database (CNKI). Results: Associations between ICD, depression, and anxiety were reported in 10 studies. In eight (of the 10) studies, ICD was associated with depression. Four studies reported associations between ICD and anxiety. Most studies had utilised cross-sectional survey designs. Conclusions: Most associations were found between ICD and depression symptoms, but effect sizes were higher between ICD and anxiety symptoms. The results have the potential to inform prevention and interventions on ICD in Eastern cultures. Future research directions are proposed.